2005
DOI: 10.1146/annurev.phyto.43.040204.135919
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Testing and Certification ofVitisandPrunusSpecies

Abstract: Strategies to screen horticultural crops for graft-transmissible agents, particularly viruses and phytoplasmas, have advanced substantially over the past decade. Tests used for Vitis and Prunus are reviewed in detail, including both biological indexing procedures and laboratory-based assays. Despite advances in laboratory molecular-based detection techniques, a strong case is presented for the continued use of slower biological tests in programs requiring high levels of confidence in detection of pathogens tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 78 publications
0
52
0
4
Order By: Relevance
“…Some of these certification schemes are in operation since the 1960s and have been delivering high quality virus indexed propagation material preventing the introduction of viruses in the fields. NCPN-FT (formerly NRSP5 or IR-2), NCPP, and FPS in the USA, CTIFL and SOC in France, EMLA and SASA in the UK, Naktuinbouw in the Netherlands, and CVIPS in Spain are only some examples to show the investment various countries have made to promote their respective agricultural economy (Boye and Desvignes, 1984;Cutting and Montgomery, 1973;Ebbels, 1979;Navarro et al, 2002;NCPN-FT 2012;Reed and Foster, 2011;Rowhani et al, 2005).…”
Section: Certification Schemes and Programmesmentioning
confidence: 99%
“…Some of these certification schemes are in operation since the 1960s and have been delivering high quality virus indexed propagation material preventing the introduction of viruses in the fields. NCPN-FT (formerly NRSP5 or IR-2), NCPP, and FPS in the USA, CTIFL and SOC in France, EMLA and SASA in the UK, Naktuinbouw in the Netherlands, and CVIPS in Spain are only some examples to show the investment various countries have made to promote their respective agricultural economy (Boye and Desvignes, 1984;Cutting and Montgomery, 1973;Ebbels, 1979;Navarro et al, 2002;NCPN-FT 2012;Reed and Foster, 2011;Rowhani et al, 2005).…”
Section: Certification Schemes and Programmesmentioning
confidence: 99%
“…Therefore, it is expected that grape plant effects on vine parameters are more linked to virus infection than to intravarietal genetic variability. Many authors have elucidated the impact of virus infections on grape performance (Rowhani et al, 2005). Cretazzo et al (2010a) observed that multiple virus infections led to very important Yield reductions in Moll.…”
Section: Analysis Of the Factors Influencing Yield Sugarmentioning
confidence: 99%
“…Preparation of plant extracts is a critical aspect of RT-PCR (Rowhani et al, 2004). Nucleic acid extraction from plant tissues is the most laborious, costly and timeconsuming step in the detection of a virus (Rowhani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nucleic acid extraction from plant tissues is the most laborious, costly and timeconsuming step in the detection of a virus (Rowhani et al, 2004). As the RT-PCR is effective in detecting several plant viruses, attempts have been made in this study to optimize simple and rapid techniques such as simpledirect-tube (SDT) method for detection of RYMV.…”
Section: Introductionmentioning
confidence: 99%